Characterization of In-House Produced Mono- and Polyclonal Antibodies Against Soy for Component-Resolved Allergen Analysis - Michael Wiederstein; Manuela Fuehrer; Kathrin Lauter; Sabine Baumgartner (Journal of Food Quality)
In recent years, food allergies have emerged as a significant global health concern that affect an increasing percentage of the population. Despite being under investigation and discussed as a major or minor elicitor of food allergies, soybean remains a notable allergenic food source, affecting approximately 0.3%–3% of people worldwide, with a higher prevalence in Asian countries. Allergic reactions to soy can manifest as mild symptoms or progress to severe, life-threatening conditions such as anaphylaxis. Consequently, there is an urgent need for the specific detection of soy allergens in food to mitigate the risk of inadvertent exposure and associated allergic reactions. State-of-the-art methods for detecting food allergens include immunoassays utilizing either food source- or, ideally, allergen-specific antibodies, along with mass spectrometry for detecting specific protein-derived peptides. However, many commercially available immunoassays predominantly utilize polyclonal antibodies, which can confirm the presence of the entire food source but lack specificity for individual allergens. In response to this limitation, the aim is to develop specific monoclonal antibodies targeting individual soy allergens. These antibodies enable “component-resolved analysis” of food samples, aligning with the emerging trend of component-resolved diagnosis in allergy research. The generated monoclonal antibodies not only offer the ability to detect individual soy allergens in food and raw materials but also serve as valuable tools for quality and safety control of materials used in oral immunotherapy and allergy diagnosis. This improvement contributes significantly to aiding people with soy allergies and can be adapted for other food allergenic sources. This advancement represents a pivotal step toward enhancing the precision and comprehensiveness of allergen detection methodologies, addresses the specific challenges faced by individuals with soy allergies, and lays the foundation for broader applications to other food allergenic sources.